Influence of air pollution on the nonaccidental death before and after the outbreak of COVID-19 - Chaohua Wei; Zhuchao Wu; Xinlan Mao; Zheyue Wang; Qiang Zhang; Weimin Kong; Jianning Xu; Jian Sun; Jianming Wang (BMC Public Health)
Abstract Background During the COVID-19 pandemic, non-therapeutic interventions (NPIs), such as traffic restrictions, work stoppages, and school suspensions, have led to a sharp decline in the concentration of air pollutants in the epidemic sites. However, few studies focused on the impact of air pollutant changes on the risk of nonaccidental death. Method We selected Yancheng City, China, as the study site and applied a Generalized Additive Model (GAM) based on the quasi-Poisson distribution to evaluate the impact of atmospheric pollutants exposure on the nonaccidental death of local residents. The time span of this study was set from January 1, 2013, to December 21, 2022, that is, before and after the outbreak of COVID-19. Results The concentration of some air pollutants has greatly varied after the outbreak of COVID-19, with a significant decline for PM2.5 (− 43.4%), PM10 (− 38.5%), SO2 (− 62.9%), and NO2 (− 22.6%), but an increase for O3 (+ 4.3%). Comparative analysis showed that PM2.5 contributed to an increased risk of nonaccidental death after the outbreak of COVID-19. With an increase in PM2.5 by 10 µg/m³, the excess relative risks (ER) of nonaccidental death of residents increased by 1.01% (95%CI: 0.19%,1.84%). The stratified analysis revealed that air pollutants impacted nonaccidental deaths in both men and women before the outbreak of COVID-19. After the outbreak of COVID-19, PM10 had a significant effect on male nonaccidental deaths. The concentrations of PM2.5, PM10, and SO2 increased by 10 µg/m³, the ER of PM2.5, PM10, and SO2 on female nonaccidental death increased by 1.52% (0.38%,2.67%), 0.58% (0.02%,1.13%), and 15.09% (5.73%,25.28%), respectively. Before the outbreak of COVID-19, five air pollutants had an impact on the death of residents from cardiovascular disease (CVD). After the outbreak of COVID-19, only PM10 significantly affected the death risk of CVD. In addition, we discovered that PM2.5, PM10, and SO2 significantly impacted the risk of death due to respiratory diseases before and after the outbreak of COVID-19. Conclusions Air pollutants have different effects on nonaccidental deaths before and after the COVID-19 outbreak. A decrease in air pollutant concentration due to the NPIs for COVID-19 had a significant effect on the reduction of the risk of nonaccidental death.